Penggunaan Google Earth Sebagai Calibrator Arah Kiblat - Riza Afrian Mustaqim (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
Qibla direction calibration is something that is very urgent in order to achieve accuracy and accuracy in facing the Qibla. Technological developments in the industrial era 4.0 require the use of technology that is easier to carry out the calibration process. Google earth which displays a virtual image of the actual earth can be an alternative in fulfilling this. This study provides a detailed description of the use of Google Earth as a Qibla direction calibrator. The method used in this research is descriptive analytical with a scientific approach. The results of this study indicate that google earth can be used as an alternative to calibrate the Qibla direction. By knowing in detail the latitude and longitude coordinates where Google Earth can determine the Qibla direction by using the measure distance and area feature (measuring distance and area) drawn straight to the Kaaba position. With regard to accuracy, as long as the location can show the updated position on Google Earth, it will be easier to calibrate, with fairly accurate results.